THE IMPACT OF THE CENTRAL BANK ON THE ECONOMIC REFORM PROCESS IN IRAQ - Reem Saeed Shihab; Fekri Ahmed Lahmood (Scholars Digest Publishing, 2025)
The central bank plays a pivotal role in establishing financial and monetary stability, which is essential for driving sustainable economic growth. In many cases, countries that have effectively implemented monetary policy and utilized its tools appropriately have seen substantial economic improvements. On the other hand, some nations have faced stagnation in economic activity due to various internal and external challenges that hindered the effectiveness of monetary policy. Iraq serves as a clear example, having endured severe economic fluctuations and structural imbalances, particularly throughout the 1990s. During that period, monetary policy was heavily influenced by central government directives, which hindered the achievement of targeted GDP levels. This study is designed to examine whether there exists a statistically significant relationship between the interest rate determined by the central bank and the real GDP index in Iraq, spanning the years 2010 to 2022. The research aims to gain insight into how the central bank has influenced the process of economic reform. One of the key findings of the study is the recommendation to safeguard the independence of the Central Bank of Iraq and avoid aligning its policies with governmental agendas. Furthermore, it emphasizes the importance of aligning monetary and fiscal policies to maximize the effectiveness of available tools in achieving economic stability.
Keywords: Central Bank, economic reform, GDP, Iraq.